Simulation training in obstetrics and gynaecology: What's happening on the frontline?. (15th June 2016) - Wilson, Erin; Janssens, Sarah; Hewett, David G.; Jolly, Brian; Beckmann, Michael
Abstract : Background: Despite evidence supporting simulation training and awareness that trainee exposure to surgery is suboptimal, it is not known how simulation is being incorporated in obstetrics and gynaecology (O&G) training across Australia and New Zealand. Aim: To investigate the current availability and utilisation of simulation training, and the attitudes, perceived barriers and enablers towards simulation in Australia and New Zealand. Method: A survey was distributed to O&G trainees and fellows in Australia and New Zealand. The survey recorded demographic data, current exposure to simulation and beliefs about simulation training. Results: The survey returned 624 responses (24.3%). Most trainees had access to at least one type of simulation (87%). Access to simulators was higher for trainees at tertiary hospitals (92% vs 76%). Few trainees had a simulation curriculum, allocated time or supervision for simulation training. 'Limited access' was the highest rated barrier to using simulation. Lack of time, other training priorities and cost were identified as further barriers. More than 80% of respondents believed simulation improves surgical skills, skills transfer to the operating theatre, and the addition of simulation to the RANZCOG curriculum would benefit trainees. However, a minority of respondents believed simulator proficiency should be shown prior to performing surgery. The need for a curriculum and supervision were highlighted as necessary supports for simulation training. Conclusions: Despite simulator availability, few trainees are supported by simulation training curricula, allocated time or supervision. Participants believed that simulation training benefits trainees and should be supported with a curriculum and teaching.